Application of magnetic motor stimulation for measuring conduction time across the lower part of the brachial plexus - Rayegani, Seyed Mansoor; Hollisaz, Mohammad Taghi; Hafezi, Rahmatollah; Nassirzadeh, Shahriar (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
Objective The objective of this study was to calculate central motor conduction time (CMCT) of median and ulnar nerves in normal volunteers. Conduction time across the lower part of the brachial plexus was measured by using magnetic stimulation over the motor cortex and brachial plexus and recording the evoked response in hand muscles.Design This descriptive study was done on 112 upper limbs of healthy volunteers. Forty-six limbs belonging to men and sixty-six belonging to women were studied by magnetic stimulation of both motor cortex and brachial plexus and recording the evoked response in thenar and hypothenar muscles. Stimulation of the motor cortex gives rise to absolute latency of each nerve whereas stimulation of the brachial plexus results in peripheral conduction time. The difference between these two values was considered the central motor conduction time (CMCT).Results In summary the result are as follows; Cortex-thenar latency = 21.4 ms (SD = 1.7), CMCT-thenar = 9.6 ms (SD = 1.9), Cortex-hypothenar latency = 21.3 ms (SD = 1.8), CMCT-hypothenar = 9.4 ms (SD = 1.8).Conclusion These findings showed that there is no meaningful difference between two genders. CMCT calculated by this method is a little longer than that obtained by electrical stimulation that is due to the more distally placed second stimulation. We recommend magnetic stimulation as the method of choice to calculate CMCT and its use for lower brachial plexus conduction time. This method could serve as a diagnostic tool for diagnosis of lower plexus entrapment and injuries especially in early stages.